2015
DOI: 10.15446/acag.v64n4.44641
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de las condiciones de cultivo, las características químicas del suelo y el manejo de grano en los atributos sensoriales de café (Coffea arabica L.) en taza

Abstract: En los municipios de Suaza y Timana se seleccionaron 55 lotes con diferentes rangos altitudinales, condiciones de manejo agronómico y beneficio, para evaluar la relación entre características químicas del suelo y manejo con los atributos sensoriales en taza. El método estadístico utilizado fue Análisis de Correspondencias Múltiples (ACM) y un análisis de PLS para determinar la relación entre los atributos sensoriales y las variables agronómicas de manejo y parámetros de suelo. Se encontro diferencias significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
7
0
4
Order By: Relevance
“…Group 3 comprises estate 7 and showed values greater than the overall mean for most variables analyzed, except for Mn (12.2mg/Kg), S (2.4mg/Kg), density (0.94g/Kg), and cup quality score (79.67%); this last variable was very similar to the overall mean of the population analyzed (80.5%). Suárez et al (2015) indicated a high association between the sensory attributes of cup quality and the chemical characteristics of the soil; furthermore, the authors determined that acid soils with high Fe and Al contents lead to intermediate and high-quality coffee cups. The same study reported that low cup quality was associated with moderately acid soils with high Cu, Zn, S contents, and low Ca and Mg contents.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Group 3 comprises estate 7 and showed values greater than the overall mean for most variables analyzed, except for Mn (12.2mg/Kg), S (2.4mg/Kg), density (0.94g/Kg), and cup quality score (79.67%); this last variable was very similar to the overall mean of the population analyzed (80.5%). Suárez et al (2015) indicated a high association between the sensory attributes of cup quality and the chemical characteristics of the soil; furthermore, the authors determined that acid soils with high Fe and Al contents lead to intermediate and high-quality coffee cups. The same study reported that low cup quality was associated with moderately acid soils with high Cu, Zn, S contents, and low Ca and Mg contents.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, this study could not establish the effect of certain soil variables on the physical and organoleptic quality of the coffee beverage. Accordingly, cup quality should be considered a multifactorial variable that depends on the genotype, environment, and the interaction between these two components (Suárez et al, 2015;Ramos and Criollo, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…; las formas móviles o disponibles de P se combinan con sesquióxidos de Fe y Al, causando inmovilización de P; además de que causa intoxicación por la solubilización de Al y Mo. En el caso del cultivo del café, la acidez del suelo tiene una gran relevancia sobre la calidad sensorial de la bebida, en suelos con altos contenidos de Fe y Al se obtiene una baja calidad de taza (Q 1 ) con bajos atributos sensoriales, mientras que, en suelos con acidez moderada, los altos contenidos de Ca ++ y Mg + , así como un adecuado porcentaje de saturación de bases, permiten alcanzar una mejor calidad de taza Q 2 (Suárez et al, 2015). El acrónimo Q se ref iere a un índice de calidad de la infusión de café, preparada y catada por un panel de expertos, quienes consideran los atributos de fragancia, aroma, acidez, sabor, cuerpo, dulzura y preferencia (Lingle, 2001).…”
Section: Resultados Y Discusión Cambios De Las Variables Edáf Icasunclassified